BIOECOLOGY AND DEVELOPMENT CHARACTERISTICS OF MAIN PESTS OF STRAWBERRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Based on the achievements of advanced science and advanced experience in the cultivation of products from the population of the Republic of Uzbekistan, from year to year achieve high and high yields of rhizomes. But this is not at the level of demand for the harvest, because part of the crop is lost due to disease. To date, about 4,000 varieties of strawberries have been created, which differ in morphological features, biological properties and uses. Strawberry pests include, first of all, root-eating weevils, tailed calf head, gamma nightshade, root sap, as well as mucous worms. But there are also pests that adapt to this berry fruit plant. Examples are the strawberry leaf and the strawberry long nose.